2017
DOI: 10.1055/s-0036-1584393
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Surgical Management of Traumatic Dislocation of the Eye Globe into the Maxillary Sinus: Report of a Rare Case and Literature Review

Abstract: We report a case of complete dislocation of the globe into the maxillary sinus, with immediate repositioning of the globe. This report highlights the importance of early surgical repair of orbital fracture and globe repositioning to regain the maximum amount of ocular functions. A review of literature found 19 cases of globe dislocation into the maxillary sinus: One case was enucleated 2 months after misdiagnosis as traumatic enucleation, six cases were documented no vision or no light perception, three cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The management of cranial-orbital injuries is currently a challenge for ophthalmologists, neurosurgeons, and neuroradiologists and requires innovative planning. Previous studies have shown that the dislocation of the globe into either the paranasal sinuses or nasal cavities [1]. In contrast, the patient in this case was suffering from a traumatic globe extruded into the anterior cranial fossa, which has been rarely reported in the literature [2].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The management of cranial-orbital injuries is currently a challenge for ophthalmologists, neurosurgeons, and neuroradiologists and requires innovative planning. Previous studies have shown that the dislocation of the globe into either the paranasal sinuses or nasal cavities [1]. In contrast, the patient in this case was suffering from a traumatic globe extruded into the anterior cranial fossa, which has been rarely reported in the literature [2].…”
Section: Discussionmentioning
confidence: 56%
“…Dislocation of the globe mainly occurs inferiorly into the maxillary sinus or medially into the ethmoid sinus following significant blunt facial trauma [1]. Only three cases of eyeball extrusion into the cranial cavity have been reported to date [2].…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 Dislocation into the maxillary sinus is most common, followed by the ethmoid sinus. 2 Even less common is dislocation into the frontal sinus 6 and the anterior cranial fossa behind the orbit. 7 No cases of globe dislocation into the sphenoid sinus have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of vision loss is high in these rare cases, it has been reported that favorable visual, functional, and aesthetic outcomes can be achieved with rapid and appropriate treatment. 1 , 2 …”
Section: Introductionmentioning
confidence: 99%
“…Among the various adverse outcomes of OBF, eyeball displacement and subsequent entrapment in the maxillary sinus are exceptionally rare [ 7 ]. A systematic literature search of English-language publications on PubMed revealed only 28 reported cases, with most complications being decreased vision, blurred vision, diplopia, and enophthalmos [ 8 ].…”
Section: Introductionmentioning
confidence: 99%